Motor Imagery Signal Classification Using Constant-Q Transform for BCI Applications - Balim, Mustafa Alper; Hanilçi, Cemal; Acir, Nurettin (European Signal Processing Conference, EUSIPCO, 2021)
Electroencephalography (EEG) signals have been using for brain-computer interface applications for the last two decades. Motor imagery (MI) signals are one of the EEG signal types formed by imagining a limb's movement. Recently with the help of deep neural networks (DNN) for classifying MI signals using time-frequency (TF) features, considerable performance improvement has been reported. This paper proposes using a well-known TF representation technique called Constant-Q Transform (CQT) for the MI signal classification. Experiments conducted on BCI IV 2b dataset with DNN classifier using CQT spectrogram show that CQT outperforms traditional short-time Fourier transform (STFT) representation.
Keywords: Brain-computer interface; Constant-Q transform; Electroencephalography; Motor imagery